IMPLIKASI KINERJA HISTORIS EKUITAS, PROFITABILITAS, DAN STRUKTUR ASET TERHADAP PREDIKSI KESEHATAN FINANSIAL LIMA BUMN KARYA TERBESAR PERIODE 2019-2024 - Riansyah, Rhonny; Alchudri, Alchudri; M. Nuh, Zulkifli; Hasanah, Nur (Komunitas Manajemen Kompetitif, 2025)
Abstract: This study was conducted on the historical financial health prediction of five Indonesian State-Owned Enterprises known as BUMN Karya which are the largest BUMN Karya for the period 2019-2024, which was triggered by the Indonesian government's plan to address the financial health problems of BUMN Karya through additional capital and mergers of these companies. In this context, this limited prediction study aims to determine whether equity, profitability and assets structure affect the financial health of the five largest BUMN Karya and are expected to be used as considerations in decision making among various decision alternatives. Data analysis uses panel data regression. The results of the study conclude that equity and profitability have a positive and significant effect, while asset structure has a negative and significant effect on the financial health of the five largest BUMN Karya. Simultaneously, the three independent variables have a positive and significant effect on the financial health of the five largest BUMN Karya.